(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Enhancing thecompetency and performance of executives has been an area of interest tomanagement philosophers and researchers for a long time. The popularization ofthe concept "Emotional Intelligence" (El) has really given a newdimension and momentum to the research initiatives that were linkingpersonality factors with the superior performance of the executives. Theconcept of cognitive intelligence, which is often referred as intelligence orIntelligent Quotient (IQ), as the sole determinant of individual performancehas been questioned with the emergence of the concept "emotionalintelligence". Consequent to the large number of research publicationsduring the last one decade, El has been identified as a critical factor in theperformance and success of individuals in varying roles in their professionalcareer and it has become an important consideration in human resource planning,job profiling, recruitment interviewing and selection, training and executivedevelopment.